Can knowledge of germline markers of toxicity optimize dosing and efficacy of cancer therapy?. (June 2012) - Crona, Daniel; Innocenti, Federico
The systemic treatment of cancer with traditional cytotoxic chemotherapeutic agents and more targeted agents is often complicated by the onset of adverse drug reactions. Pharmacogenetic prediction of adverse drug reactions might have consequences for dosing and efficacy. This review discusses relevant examples where the germline variant–toxicity relationship has been validated as an initial step in developing clinically useful pharmacogenetic markers and provides examples where germline variants have influenced dosing strategies and/or survival or other outcomes of efficacy. This review will also provide insight into the reasons why more pharmacogenetic markers have not been routinely integrated into clinical practice.